PENGARUH SELF HELP GROUP TERHADAP TINGKAT PENGETAHUAN PENDERITA TENTANG PENCEGAHAN PENULARANTB PARU - Dwi W, Binarti (JURNAL KEPERAWATAN SEHAT, 2016)
TBC incident increases on lately decade in the world as well as in Indonesia. One influence factor of people’s knowledge level is information. This information can be obtained by the sufferers in a way of coming up to share information and experience along with overall problems or it’s called as self-help group. The purposed of this research was prove the influence of self-help group toward level of sufferers knowledge about spreading prevention of TB lung in Kintelan and Medali Village at Puri Subdistrict Mojokerto Regency. The research used pre-experimental design with One-Group Pre-Post Test Design. Population in this research were 19 TB lung sufferers in Kintelan and Medali Village at Puri Subdistrict Mojokerto Regency. The sampling technique was used purposive sampling with sample 12 respondents taken in accordance with criteria. The instrument of research used questionnaire of 12 questions. Independent variable in this research were self help group and dependent variable was the level of sufferers knowledge about spreading prevention of TB lung. The test result of Wilcoxon Signed Rank Test revealed that p value (0,003) < α (0,05) it mean there was influence of self-help group toward level of sufferers’ knowledge about spreading prevention of TB lung in Kintelan and Medali Village at Puri Subdistrict Mojokerto Regency. The increase of respondents knowledge about spreading prevention TB lung are influenced by information, liveliness respondents and education factor.